2018
DOI: 10.1111/1541-4337.12396
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Unravel Nutraceutical Potential of Edible Seaweeds: An Emerging Source of Functional Food

Abstract: Functional foods are nutritional compounds which also provide health and medicinal benefits. Daily food intake has much impact on the quality of life, and therefore inclusion of functional foods is now essential to our diet. Nutraceuticals are neither food nor drug but are added to food to provide extra nutritional and physiological properties. Though nutraceutical compounds provide minimal actions, their regular involvement in the diet can provide major and long‐term health benefits. Global demand for additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 143 publications
(191 reference statements)
1
64
0
2
Order By: Relevance
“…Seaweeds are considered a good source of protein, as they contain all essential amino acids, acidic amino acids, and conditional essential amino acids (Tanna & Mishra, ). Amino acid profiling of selected seaweeds confirmed that they contain higher concentration of some essential amino acids than the milk and egg protein consumed worldwide (Øverland, Mydland, & Skrede, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seaweeds are considered a good source of protein, as they contain all essential amino acids, acidic amino acids, and conditional essential amino acids (Tanna & Mishra, ). Amino acid profiling of selected seaweeds confirmed that they contain higher concentration of some essential amino acids than the milk and egg protein consumed worldwide (Øverland, Mydland, & Skrede, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid, also known as vitamin C, is a water‐soluble vitamin that is widely used to avoid common infections, and ascorbic‐acid rich seaweeds are considered a potential dietary supplement or food additive (Tanna & Mishra, ). In our study, we observed that all the selected tropical seaweeds (except CRM and SL) possessed high amounts of ascorbic acid, especially Ulva spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seaweeds are macroalgae, with high nutritional, nutraceutical, and medicinal properties (Cunha & Grenha, ; Hamed, Özogul, Özogul, & Regenstein, ; Ito & Hori, ; Kılınç, Cirik, Turan, Tekogul, & Koru, ; Mabeau & Fleurence, ; Pereira, ; Rupérez, Gómez‐Ordóñez, & Jiménez‐Escrig, ; Tanna & Mishra, ). Asian and European countries use seaweeds as fertilizers for agriculture, as well as thickening and gelling agents for industrial applications (Kılınç et al., ; Kraan, ).…”
Section: Introductionmentioning
confidence: 99%